Best Practices of Local Wisdom Oriented Islamic Education Management for Fostering Intercultural Sensitivity in Vocational Tourism Schools - Hafizin, Hafizin; Maisyaroh, Maisyaroh; Timan, Agus; Triwiyanto, Teguh (Yayasan Keluarga Guru Mandiri, 2026)
Indonesia's multicultural landscape poses both opportunities and challenges for vocational education, particularly in preparing tourism students to develop intercultural sensitivity while sustaining local cultural identity. This study explores the role of integrating Sasak local wisdom into the management of Islamic Religious Education (IRE) to strengthen student intercultural competence in West Lombok. Using a mixed-methods approach, qualitative case studies were conducted at SMKN 1 Batulayar and SMKN 1 Lingsar, including interviews, classroom observations, and document analysis. The results indicate that students generally demonstrated moderate to high levels of intercultural sensitivity, with notable variations across dimensions. Students at SMKN 1 Lingsar showed stronger engagement in cross-cultural interactions, whereas those at SMKN 1 Batulayar exhibited a higher level of self-confidence. Qualitative findings further reveal that effective lesson planning, inter-teacher collaboration, contextual learning practices, and active community involvement play a crucial role in embedding local cultural values within IRE. This study concludes that integrating local wisdom and religious education contributes to the development of an inclusive character. It fosters tolerance and enhances students' readiness to navigate a multicultural tourism environment. From a theoretical perspective, this research advances the discourse on intercultural education by proposing a dual-path intercultural sensitivity model encompassing collaborative and experiential pathways as a novel framework for strengthening cultural responsiveness in vocational schools.